MECHANISMS OF COOPERATION BETWEEN STATE AND CIVIL SOCIETY INSTITUTIONS IN THE SOCIAL SUPPORT OF YOUTH IN UZBEKISTAN (Global Conference on Multidisciplinary Research and Innovation, 2026)
This research paper explores the evolving mechanisms of cooperation between state bodies and civil society institutions (CSIs) in the Republic of Uzbekistan, specifically within the domain of youth social support. The study analyzes the transition from a state-centric model to a system of social partnership, emphasizing the synergistic integration of "spiritual processes" (ma’naviy jarayonlar) with modern digital technologies. Drawing upon the theoretical frameworks of Robert Putnam (social capital), Jürgen Habermas (public sphere), and Manuel Castells (network society), the paper examines how this cooperation fosters both the socio-economic empowerment of youth and their "spiritual immunity" against ideological threats. The research highlights that a robust partnership—where the state provides legal and financial resources while civil society offers grassroots engagement—is essential for ensuring long-term social stability and the development of human capital in the "Third Renaissance."
Keywords: Youth Policy, Civil Society Institutions, Social Partnership, Uzbekistan, Social Capital, Spiritual Processes, Digital Transformation, NGOs, State Governance, Social Innovation.